LEGAL ASPECTS OF PROTECTION OF CHILDREN AND WOMEN VICTIMS OF CRIME IN INDONESIA - Yusrizal Yusrizal; Budi Bahreisy; Ferdy Saputra (NOMOI Law Review, 2021)
The protection of victims of crime in the Indonesian legal system has not received serious attention. This can be seen from the reality of enforcement is still at least the fulfillment of the rights of victims of crime. The imbalance of protection of victims of crime with perpetrators of crimes is basically one of the denials of the principle that every citizen has a common position in law and justice. The purpose of this writing is to find out the still unfulfilled rights of victims of crime, especially the rights of children and women. Research method used is normative juridical approach is an approach that is done based on the main legal material by studying theories, concepts, legal principles and laws and regulations related to this writing. Looking at the position of the victim there is actually no detailed provision on the form of victim protection so as to cause an imbalance in the legal gap between the victim and the perpetrator of the crime that will ultimately lead to injustice. Therefore, the government and legislature need to reformulate and draft legislation that specifically regulates the protection of victims of crime, in which will be regulated in terms of comprehensive protection of victims of crime, such as physical, financial, psychic, and medical protection.Keywords: Legal Protection. Victims, Children and Women